1980
DOI: 10.1159/000112379
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Metabolism and Glycine Synthase Activity during the Postnatal Development of Rat Brain

Abstract: Glycine synthase from rat brain mitochondria shows an apparent Km for glycine of 2.6 mM. Glycine synthase from rat brain homogenate has a maximum of activity at the 10th day of life. However, each area of the central nervous system shows a different developmental pattern of glycine synthase activity. Both the 14COa production from (U-14C)-glycine and the incorporation of the radioactivity from the (U-14C)-glycine to the acid-insoluble fraction by cortex sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Autoradiographic studies of hippocampus slices have demonstrated that glycine is taken up into astrocytes (Fedele et al, 1993), where the degradation of two glycine molecules produces serine (Daly et al, 1976). This pathway may be relevant to D-serine synthesis, because D-serine is probably concentrated in many of the same protoplasmic astrocytes, and the ontogeny of glycine cleavage activity in cerebellum (Lahoya et al, 1980) closely follows that of D-serine (Fig. 6).…”
Section: Discussionmentioning
confidence: 97%
“…Autoradiographic studies of hippocampus slices have demonstrated that glycine is taken up into astrocytes (Fedele et al, 1993), where the degradation of two glycine molecules produces serine (Daly et al, 1976). This pathway may be relevant to D-serine synthesis, because D-serine is probably concentrated in many of the same protoplasmic astrocytes, and the ontogeny of glycine cleavage activity in cerebellum (Lahoya et al, 1980) closely follows that of D-serine (Fig. 6).…”
Section: Discussionmentioning
confidence: 97%
“…We observed highest glycine concentrations at P10. Others have reported that the rate of glycine synthesis peaks around 10–15 days after birth (Lahoya et al. 1980; Benítez‐Diaz et al.…”
Section: Discussionmentioning
confidence: 99%
“…Like for NAAG, the highest glycine concentrations in the brain are observed at P10 and decline until adulthood (Kulak et al, 2010). In fact, the rate of glycine synthesis peaks around 10-15 days after birth (Benítez-Diaz et al, 2003;Lahoya et al, 1980) and likewise, during this period, glycine receptors undergo a major switch of the relative expression of glycinergic subunits (Lynch, 2004). It is interesting to note that the increase in levels of excitatory neurotransmitters, glutamate and aspartate (NMDA receptor agonists), is paralleled by a reduction in the concentration of its modulator NAAG as well as its co-agonist glycine.…”
Section: Neurotransmitter Metabolismmentioning
confidence: 99%